Engendering effectiveness : a feminist critique of the new aid architecture - Pérez Piňán, Astrid Vanessa (Irish School of Ecumenics, 2015)
This study is concerned with the absence of gender-sensitive indicators oriented towards human rights and human development goals in the Paris Declaration of Aid Effectiveness - the main international agreement to make official development aid more effective. The thesis takes issue with the technocratic approach of the new aid agenda and argues for gender-sensitive indicators of aid effectiveness. Using Feminist Political Economy as theoretical framework, the study draws on secondary data (policy documents, newspapers, independent studies, a range of reports, and the academic literature), and uses a case study based on Nicaragua supplemented by primary data (semi-structured interviews) to assess, critique and develop a framework for gender-sensitive indicators to measure aid effectiveness.
Keywords: Religions, Peace Studies & Theology, Ph.D.; Ph.D. Trinity College Dublin.